Spirituality in higher education autoethnographies - Chang, Heewon, 1959-; Boyd, Drick (Walnut Creek, Calif. : Left Coast Press, Inc., 2011)
"This collection of articles explores how a wide range of academics-- diverse in location, rank and discipline-- understand and express how they deal with spirituality in their professional lives and how they integrate spirituality in teaching, research, administration, and advising. The contributors also analyze the culture of academia and its challenges to the spiritual development of those involved. Twenty chapter authors--from a variety of faith traditions--discuss the ways in which their own beliefs have affected their journeys through higher education. By using an autoethnographic, self-analytical lens, this collection shows how various spiritualities have influenced how higher education is understood, taught and performed. The book will stimulate debate and conversations on a topic traditionally ignored in academia"-- Provided by publisher.
pt. 1. Spirituality and personhood -- pt. 2. Spirituality and teaching -- pt. 3. Spirituality, scholarship, and outreach.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Universities and colleges -- Religion; College teaching -- Religious aspects; College teachers -- Conduct of life; College administrators -- Conduct of life; Spirituality; Electronic books